2008
DOI: 10.1016/j.ypmed.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity as a strategy for maintaining tobacco abstinence: A randomized trial

Abstract: Physical activity as a strategy for maintaining tobacco abstinence: a randomized trial. Objectives. For smoking cessation, physical activity (PA) may help manage withdrawal symptoms, mood, stress, and weight; yet studies of PA as an aid for smoking cessation have been mixed. This study examined: A B S T R A C T A R T I C L E I N F O(1) the impact of an extended relapse prevention program on increasing moderate to vigorous PA (MVPA) in adults enrolled in a tobacco cessation treatment trial; (2) whether changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 48 publications
(39 reference statements)
2
68
0
5
Order By: Relevance
“…So, we can hypothesize that living in a supportive and friendly family environment is a significant factor in preventing smoking in adolescent. Studies investigating Asian Pacific Journal of Cancer Prevention, Vol 14, 2013 7287 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.12.7283 Refusal Self Efficacy, Self Esteem, Smoking Refusal Skills and Water Pipe Smoking by Iranian Male Adolescents the association between smoking and physical activity have yielded mixed results (Trinh, 2005;Prochaska et al, 2008;Vandita et al, 2008). While most have found physical activity to be protective against smoking (Trinh, 2005;Nelson and Gordon-Larsen, 2006), others have found physical activity to be associated with higher rates of smoking (Prochaska et al, 2008;Vandita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…So, we can hypothesize that living in a supportive and friendly family environment is a significant factor in preventing smoking in adolescent. Studies investigating Asian Pacific Journal of Cancer Prevention, Vol 14, 2013 7287 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.12.7283 Refusal Self Efficacy, Self Esteem, Smoking Refusal Skills and Water Pipe Smoking by Iranian Male Adolescents the association between smoking and physical activity have yielded mixed results (Trinh, 2005;Prochaska et al, 2008;Vandita et al, 2008). While most have found physical activity to be protective against smoking (Trinh, 2005;Nelson and Gordon-Larsen, 2006), others have found physical activity to be associated with higher rates of smoking (Prochaska et al, 2008;Vandita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an extended adult intervention study using pedometers and fitness counseling found that moderate/vigorous physical activity was positively associated with sustained smoking abstinence at 24 weeks. 9 Interestingly, women had significantly higher quit rates in a cessation intervention, compared with programs with no fitness component. 4 Ultimately, Ussher et al 3 concluded that there is no harm in encouraging physical activity as a smokingcessation aid, because there is no evidence that it interferes with cessation.…”
mentioning
confidence: 99%
“…4 Ultimately, Ussher et al 3 concluded that there is no harm in encouraging physical activity as a smokingcessation aid, because there is no evidence that it interferes with cessation. Dual intervention efforts seem logical, because a majority of youth and adult smokers are physically inactive 9 and a large body of evidence demonstrates the critical importance of physical activity for health throughout the life span. 2 The research described above focused exclusively on adults, but there is evidence that physical activity, ranging from aerobic activities (eg, team sports) to less-vigorous activities (eg, walking), is protective against smoking initiation and acceleration among youths.…”
mentioning
confidence: 99%
“…Al igual que en el estudio de Read et al, (2001) el tipo de ejercicio preferido fue caminar, especialmente en el caso de las mujeres. Los pacientes se mostraron igualmente dispuestos a utilizar podómetros como medida de registro de su evolución, instrumento cuya utilización se ha demostrado que favorece el incremento de la motivación y los niveles de actividad física tanto en población general (Bravata et al, 2007) como en fumadores (Prochaska et al, 2008). intensidad de las sesiones deberían ser mayores y, en cualquier caso, teniendo presente que el control del peso mediante ejercicio físico no es inmediato -al requerir tiempo para compensar el gasto energético-debería adecuarse tanto el volumen y la intensidad de las sesiones (Blundell, Stubbs, Hughes, Whybrow y King, 2003;Chaput et al, 2011), como su frecuencia, preferiblemente diaria.…”
Section: Efecto Del Ejericicio Físico En El Tratamiento De La Dependeunclassified